A Label-Based Polymer Nanoparticles Biosensor Combined with Loop-Mediated Isothermal Amplification for Rapid, Sensitive, and Highly Specific Identification of Brucella abortus - Yang, Xinggui; Wang, Yue; Liu, Ying; Huang, Junfei; Tan, Qinqin; Ying, Xia; Hu, Yong; Li, Shijun (Frontiers in Bioengineering and Biotechnology, 2021)
Brucella abortus (B. abortus), an important zoonotic pathogen in Brucella spp., is the major causative agent of abortion in cattle (namely, bovine brucellosis). Currently, although the isolation and identification of the Brucella abortus were commonly accepted as the gold standard method, it cannot meet the requirements for early diagnostic strategies. Conventional PCR techniques and immunological tests can realize rapid detection of B. abortus, but the demands for PCR thermal cyclers and/or specific antibodies hinder their application in basic laboratories. Thus, rapid, sensitive, and specific diagnostic strategies are essential to prevent and control the spread of the bovine brucellosis. In this work, a novel detection method for the rapid identification of B. abortus, which uses loop-mediated isothermal amplification (LAMP) combined with a label-based polymer nanoparticles lateral flow immunoassay biosensor (LFIA), was established. One set of specific B. abortus-LAMP primers targeting the BruAb2_0168 gene was designed by the online LAMP primer design tool. The B. abortus-LAMP-LFIA assay was optimized and evaluated using various pathogens and whole blood samples. The optimal amplification temperature and time for B. abortus-LAMP-LFIA were determined to be 65°C and 50 min, respectively. The B. abortus-LAMP-LFIA method limit of detection (LoD) was 100 fg per reaction for pure genomic DNA of B. abortus. Meanwhile, the detection specificity was 100%, and there was no cross-reactivity for other Brucella members and non-Brucella strains. Furthermore, the entire procedure, including the DNA preparation for whole blood samples (30 min), isothermal incubation (50 min), and LFIA detection (2–5 min), can be completed in approximately 85 min. Thus, the B. abortus-LAMP-LFIA assay developed was a simple, rapid, sensitive, and reliable detection technique, which can be used as a screening and/or diagnostic tool for B. abortus in the field and basic laboratories.